2023
DOI: 10.30773/pi.2023.0105
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Metabolic Risk Factors and Cognitive Impairment in Schizophrenia Based on Sex

Hongna Huang,
Lizhao Du,
Zhengping Pu
et al.

Abstract: Objective Sex differences have been observed in many aspects of schizophrenia, including cognitive deficits. Despite extensive research into the relationship between metabolic factors and cognitive deficits in schizophrenia, few studies have explored the potential sex difference in their association.Methods We recruited 358 schizophrenia patients and 231 healthy controls. The participants underwent measurements of body mass index (BMI), waist circumference, blood pressure, triglycerides, high-density lipoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Our study revealed significant differences in neuropsychological performance, anthropometric measurements, and biochemical markers between male schizophrenic patients and healthy controls. These differences are consistent with the recently published findings of Huang et al (2023), who investigated the association between metabolic risk factors and cognitive impairment in schizophrenia [17]. Higher scores in TMT and Stroop tests among the SZ group indicate worse neuropsychological performance, mirroring the observations of Cao et al (2023) regarding the impact of metabolic syndrome on cognitive function and the benefits of psychological interventions [18].…”
Section: Key Findingssupporting
confidence: 91%
“…Our study revealed significant differences in neuropsychological performance, anthropometric measurements, and biochemical markers between male schizophrenic patients and healthy controls. These differences are consistent with the recently published findings of Huang et al (2023), who investigated the association between metabolic risk factors and cognitive impairment in schizophrenia [17]. Higher scores in TMT and Stroop tests among the SZ group indicate worse neuropsychological performance, mirroring the observations of Cao et al (2023) regarding the impact of metabolic syndrome on cognitive function and the benefits of psychological interventions [18].…”
Section: Key Findingssupporting
confidence: 91%